no entiendo


porqué es mediodifícil dar un ejemplo que ilustre la Regla de la Cadena para una composición de dos funciones escalares

{\mathbb{R}}\stackrel{f}\to{\mathbb{R}}\stackrel{g}\to{\mathbb{R}}

donde todo lo que hay que hacer es (g\circ f)'(p)=g'(fp)\cdot f'(p).

Este problem persiste aunque la persona ya haya entendido como es en el caso más general: {\mathbb{R}}^n\stackrel{F}\to{\mathbb{R}}^m\stackrel{G}\to{\mathbb{R}}^l

donde se va a cumplir J(G\circ F)(p)=JG(Fp)\cdot JF(p). Aveces usamos la notación J(G\circ F)|_p=JG(|_{Fp})\cdot JF|_p

Dejenme explicar con este ejemplo:

Si f(t)=t^2 y g(t)=t^3+1 entonces g\circ f(t)=t^6+1.

Si la posición inicial es t=-2 entonces:

f(-2)=4

(g\circ f)'(t)=6t^5

(g\circ f)'(-2)=-192.

Por otro lado

f'(-2)=-4

y

g'(f(-2))=g'(4)=48

entonces también

g'(f(-2))\cdot f'(-2)=(-4)(48)=-192.

Leave a comment

Filed under math

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s